Recycled aggregate treating agent and recycled aggregate
By using regenerated aggregate treatment agents with components such as polyvinyl alcohol, chitosan, polysiloxane and hydrophilic modified nanosilica sol, the mechanical properties and structural stability of the regenerated aggregate are improved, and the current solution is solved There is a problem of poor performance of recycled aggregates, which improves the overall performance of recycled concrete.
Patent Information
- Application Number
- CN202011346170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-11-26
AI Technical Summary
The existing recycled aggregates have defects in mechanical properties, and their porosity is large and there is a lot of mortar attached to the surface, which hinders the effective use of waste concrete.
Using a regenerated aggregate treatment agent, the treatment agent includes polyvinyl alcohol, chitosan, polysiloxane, hydrophilic modified nanosilica sol and penetrant, the performance of the regenerated aggregate is improved by immersion and stirring treatment. .
By improving the interface transition zone and mortar structure of the regenerated aggregate, its mechanical properties and stability are improved, porosity and water absorption are reduced, and the durability and frost resistance of the regenerated concrete are improved.
Smart Images

Figure BDA0002799995180000061 
Figure BDA0002799995180000062
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to a recycled aggregate treating agent and also provides a recycled aggregate. Background Art
[0002] With the rapid development of my country's construction industry, the use of concrete has increased year by year, and the aggregate resources, which are the most consumed in concrete preparation, are decreasing. At the same time, a huge amount of construction waste has been generated, the most important of which is waste concrete. In addition to being used as landfill materials, waste concrete can also be used as the foundation of buildings and roads. However, a large amount of waste concrete is still placed in landfills, occupying a large area and polluting the environment.
[0003] Waste concrete contains a large amount of sand and gravel aggregates. Aggregates formed by crushing, screening, grading, cleaning and mixing waste concrete in a certain proportion are called recycled aggregates, among which aggregates with a particle size of 0.5-5mm are called recycled fine aggregates, and those with a particle size of 5-40mm are called recycled coarse aggregates. With the cost of natural aggregate mining increasing year by year, if the sand and gravel aggregates in waste concrete can be reasonably utilized, it can not only reduce the use of natural aggregates, but also reduce the pollution of waste concrete to the environment.
[0004] However, due to the large amount of old mortar in the recycled aggregate, it has certain defects in various mechanical properties compared with ordinary concrete, and the processing mechanism of recycled aggregate concrete technology is not yet perfect, and there are still many bottlenecks that need to be broken through to improve various mechanical performance indicators. For example, the commonly used crushing method is difficult to completely crush the waste concrete, and the produced aggregate has some problems, such as rough and uneven surface containing many micro cracks and old cement mortar, many edges and corners, high crushing index, high porosity and water absorption, etc. Therefore, the performance is poorer than that of natural aggregate. Affected by this, the durability and frost resistance of recycled concrete are also worse than ordinary concrete.
[0005] According to relevant research, whether it is tensile failure or compressive failure of recycled aggregate concrete, it is manifested as the fracture of old mortar and the destruction of the interface transition zone, and the initial microcracks in the destruction process often appear first in the interface transition zone, and then extend and expand to the mortar area. Therefore, the interface transition zone is the weakest link of recycled aggregate concrete, and the main factor causing this phenomenon is the presence of old mortar. Old mortar greatly affects the differences in the number, distribution and performance of the interface transition zone.
[0006] Disadvantages of recycled aggregates, such as large porosity, poor foundation performance, and excessive mortar attached to the surface, have always hindered the utilization of waste concrete. In addition to improving the performance of recycled aggregates from both physical and chemical aspects, existing modification methods also improve concrete performance by adding active substances and other materials during the preparation of recycled concrete. However, at present, whether it is physical methods (such as mechanical grinding, particle shaping, etc.) or chemical methods (such as chemical immersion, etc.), the recycled aggregates produced are still far behind new aggregates. Summary of the invention
[0007] Technical problem: In order to solve the defects of the prior art, the purpose of the present invention is to provide a recycled aggregate treatment agent and a recycled aggregate.
[0008] Technical solution: The present invention provides a recycled aggregate treatment agent, comprising the following components in parts by weight: 30-50 parts of polyvinyl alcohol, 5-15 parts of chitosan, 5-15 parts of polysiloxane, 6-10 parts of hydrophilic modified nano-silica sol, 10-20 parts of penetrant, and 60-80 parts of deionized water.
[0009] Preferably, the recycled aggregate treatment agent comprises the following components in parts by weight: 40 parts of polyvinyl alcohol, 10 parts of chitosan, 10 parts of polysiloxane, 8 parts of hydrophilically modified nano-silica sol, 15 parts of penetrant, and 67 parts of deionized water.
[0010] Preferably, the hydrophilic modified nano-silica sol is made of the following components in parts by weight: 20-25 parts of nano-silica, 0.3-0.4 parts of vinyl triethoxysiloxane, 0.5-1.0 parts of maleic anhydride, 2.0-4.0 parts of acrylic acid, 0.5-1 parts of hydroxyethyl acrylate, 0.1-0.3 parts of dibenzoyl peroxide, 0.1-0.3 parts of polyvinyl alcohol, and 65-75 parts of anhydrous ethanol.
[0011] The present invention also provides a method for preparing the above-mentioned recycled aggregate treating agent, comprising the following steps:
[0012] (1) Preparation of hydrophilic modified nano-silica sol: Add nano-silica to anhydrous ethanol, stir at 40-50°C for 5-10 minutes, then add vinyl triethoxysiloxane, and continue to stir and react for 20-30 minutes; add maleic anhydride, acrylic acid, and hydroxyethyl acrylate again, continue to stir and react for 10-15 minutes, then add dibenzoyl peroxide, heat to 70-80°C and react for 2-3 hours; then add polyvinyl alcohol and stir until completely dissolved to obtain hydrophilic modified nano-silica sol;
[0013] (2) dissolving polyvinyl alcohol in deionized water, stirring at 90-95° C. for 30-60 minutes, and cooling to obtain a polyvinyl alcohol solution;
[0014] (3) Add chitosan, polysiloxane and hydrophilic modified nano-silica sol into the polyvinyl alcohol solution, stir and react at 50-60° C. for 20-40 minutes; then add the penetrant and stir evenly to obtain the product.
[0015] In step (3), the penetrant is isobutyltriethoxysilane.
[0016] The present invention also provides a recycled aggregate with excellent performance, which is obtained by treating the recycled aggregate with the above-mentioned recycled aggregate treating agent.
[0017] The present invention also provides a method for processing the above-mentioned recycled aggregate, comprising the following steps:
[0018] (1) Stirring the crushed waste concrete at 50-70°C for 20-40 minutes and washing with water; stirring at 50-70°C for 20-40 minutes and washing with water, and obtaining recycled aggregate to be processed;
[0019] (2) soaking the recycled aggregate pretreated in step (1) in the recycled aggregate treatment agent according to any one of claims 1 to 3;
[0020] (3) After soaking, the recycled aggregate is cleaned to remove impurities and dried.
[0021] In step (2), the soaking treatment time is 12-24 hours.
[0022] In step (3), the drying temperature is 50-60° C. and the drying time is 10-12 h.
[0023] Beneficial effects: The hydrophilic modified nano-silica sol and chitosan in the recycled aggregate treatment agent provided by the present invention can penetrate into the smaller voids inside the recycled aggregate to form a bonding layer with the coarse aggregate and the mortar in the interface transition zone, thereby ensuring the stability of the interface transition zone. At the same time, they can also penetrate into the mortar to fill the mortar, thereby ensuring the stability of the old mortar structure. Polyvinyl alcohol and polysiloxane can penetrate into larger voids and the surface of the aggregate, thereby ensuring the structural stability of the large pores of the aggregate. At the same time, chitosan forms a stable structure between the water-modified nano-silica sol, polyvinyl alcohol and polysiloxane, thereby ensuring the stability of the overall structure of the recycled aggregate. DETAILED DESCRIPTION
[0024] The following examples are given to further describe the present invention in detail in conjunction with specific embodiments. The following examples are only intended to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0025] The experimental methods in the following examples are conventional experimental methods unless otherwise specified. The raw materials, experimental reagents, etc. used in the examples are commercially available products unless otherwise specified.
[0026] Example 1
[0027] The recycled aggregate treatment agent comprises the following components in parts by weight: 30 parts of polyvinyl alcohol, 5 parts of chitosan, 15 parts of polysiloxane, 6 parts of hydrophilic modified nano silica sol, 10 parts of penetrant and 60 parts of deionized water.
[0028] The hydrophilic modified nano silica sol is prepared from the following components in parts by weight: 20 parts of nano silica, 0.3 parts of vinyl triethoxysiloxane, 0.5 parts of maleic anhydride, 2.0 parts of acrylic acid, 0.5 parts of hydroxyethyl acrylate, 0.1 parts of dibenzoyl peroxide, 0.1 parts of polyvinyl alcohol, and 65 parts of anhydrous ethanol.
[0029] The preparation method of the above-mentioned recycled aggregate treatment agent comprises the following steps:
[0030] (1) Preparation of hydrophilic modified nano-silica sol: Add nano-silica to anhydrous ethanol, stir at 40°C for 10 minutes, then add vinyl triethoxysiloxane, and continue to stir and react for 30 minutes; once again add maleic anhydride, acrylic acid, and hydroxyethyl acrylate, continue to stir and react for 15 minutes, then add dibenzoyl peroxide, heat to 70°C and react for 3 hours; then add polyvinyl alcohol and stir until completely dissolved to obtain hydrophilic modified nano-silica sol;
[0031] (2) dissolving polyvinyl alcohol in deionized water, stirring at 90° C. for 60 minutes, and cooling to obtain a polyvinyl alcohol solution;
[0032] (3) Add chitosan, polysiloxane and hydrophilic modified nano-silica sol into the polyvinyl alcohol solution, stir and react at 50° C. for 40 minutes; then add the penetrant isobutyl triethoxysilane and stir evenly to obtain the product.
[0033] Example 2
[0034] The recycled aggregate treatment agent comprises the following components in parts by weight: 50 parts of polyvinyl alcohol, 15 parts of chitosan, 5 parts of polysiloxane, 10 parts of hydrophilic modified nano silica sol, 20 parts of penetrant and 80 parts of deionized water.
[0035] The hydrophilic modified nano-silica sol is prepared from the following components in parts by weight: 25 parts of nano-silica, 0.4 parts of vinyl triethoxysiloxane, 1.0 parts of maleic anhydride, 4.0 parts of acrylic acid, 1 part of hydroxyethyl acrylate, 0.3 parts of dibenzoyl peroxide, 0.3 parts of polyvinyl alcohol, and 75 parts of anhydrous ethanol.
[0036] The preparation method of the above-mentioned recycled aggregate treatment agent comprises the following steps:
[0037] (1) Preparation of hydrophilic modified nano-silica sol: Add nano-silica to anhydrous ethanol, stir at 50°C for 5 minutes, then add vinyl triethoxysiloxane, and continue to stir and react for 20 minutes; add maleic anhydride, acrylic acid, and hydroxyethyl acrylate again, continue to stir and react for 10 minutes, then add dibenzoyl peroxide, heat to 80°C and react for 2 hours; then add polyvinyl alcohol and stir until completely dissolved to obtain hydrophilic modified nano-silica sol;
[0038] (2) dissolving polyvinyl alcohol in deionized water, stirring at 95° C. for 30 minutes, and cooling to obtain a polyvinyl alcohol solution;
[0039] (3) Add chitosan, polysiloxane and hydrophilic modified nano-silica sol into the polyvinyl alcohol solution, stir and react at 60° C. for 20 min; then add the penetrant isobutyltriethoxysilane and stir evenly to obtain the product.
[0040] Example 3
[0041] The recycled aggregate treatment agent comprises the following components in parts by weight: 40 parts of polyvinyl alcohol, 10 parts of chitosan, 10 parts of polysiloxane, 8 parts of hydrophilic modified nano silica sol, 15 parts of penetrant and 67 parts of deionized water.
[0042] The hydrophilic modified nano-silica sol is prepared from the following components in parts by weight: 22 parts of nano-silica, 0.35 parts of vinyl triethoxysiloxane, 0.8 parts of maleic anhydride, 3.0 parts of acrylic acid, 0.8 parts of hydroxyethyl acrylate, 0.2 parts of dibenzoyl peroxide, 0.2 parts of polyvinyl alcohol, and 70 parts of anhydrous ethanol.
[0043] The preparation method of the above-mentioned recycled aggregate treatment agent comprises the following steps:
[0044] (1) Preparation of hydrophilic modified nano-silica sol: Add nano-silica to anhydrous ethanol, stir at 45°C for 8 minutes, then add vinyl triethoxysiloxane, and continue to stir and react for 25 minutes; once again add maleic anhydride, acrylic acid, and hydroxyethyl acrylate, continue to stir and react for 13 minutes, then add dibenzoyl peroxide, heat to 75°C and react for 2.5 hours; then add polyvinyl alcohol and stir until completely dissolved to obtain hydrophilic modified nano-silica sol;
[0045] (2) dissolving polyvinyl alcohol in deionized water, stirring at 92° C. for 45 minutes, and cooling to obtain a polyvinyl alcohol solution;
[0046] (3) Add chitosan, polysiloxane and hydrophilic modified nano-silica sol into the polyvinyl alcohol solution, stir and react at 55° C. for 30 minutes; then add the penetrant isobutyl triethoxysilane and stir evenly to obtain the product.
[0047] Example 4
[0048] The recycled aggregate is treated with the recycled aggregate treating agent of Example 1, and the method comprises the following steps:
[0049] (1) The crushed waste concrete is stirred at 50°C for 40 minutes and rinsed with water; then stirred at 50°C for 40 minutes and rinsed with water, and the obtained recycled aggregate is to be processed;
[0050] (2) soaking the recycled aggregate pretreated in step (1) in the recycled aggregate treatment agent of Example 1 for 24 hours;
[0051] (3) After soaking, the recycled aggregate is cleaned of impurities and dried at a temperature of 50°C for 12 hours.
[0052] Example 5
[0053] The recycled aggregate is treated with the recycled aggregate treating agent of Example 2, and the method comprises the following steps:
[0054] (1) The crushed waste concrete is stirred at 70°C for 20 minutes and rinsed with water; then stirred at 70°C for 20 minutes and rinsed with water, and the obtained recycled aggregate is ready for treatment;
[0055] (2) soaking the recycled aggregate pretreated in step (1) in the recycled aggregate treatment agent of Example 2 for 24 hours;
[0056] (3) After soaking, the recycled aggregate is cleaned of impurities and dried at a temperature of 60°C for 10 hours.
[0057] Example 6
[0058] The recycled aggregate is treated with the recycled aggregate treating agent of Example 3, and the method comprises the following steps:
[0059] (1) The crushed waste concrete is stirred at 60°C for 30 minutes and rinsed with water; then stirred at 60°C for 30 minutes and rinsed with water, and the obtained recycled aggregate is to be processed;
[0060] (2) soaking the recycled aggregate pretreated in step (1) in the recycled aggregate treatment agent of Example 3 for 18 hours;
[0061] (3) After soaking, the recycled aggregate is cleaned of impurities and dried; the drying temperature is 55°C and the drying time is 101 hours.
[0062] A batch of concrete blocks were prepared using the recycled aggregates of Examples 4 to 6. The formula is shown in Table 1 and the method was conventional.
[0063] Table 1
[0064]
[0065] The concrete blocks are placed in clean water and salt water (sodium chloride aqueous solution with a mass concentration of 30%) and cured to the specified age. The flexural strength of the concrete is tested using a concrete pressure testing machine, and its resistance to chloride ion corrosion is characterized by its flexural strength and corrosion resistance coefficient.
[0066] Table 2
[0067]
[0068] It is obvious to those skilled in the art that the above description of the specific embodiments of the present invention does not limit the application of the present invention, and various equivalent substitutions or modifications can be made according to actual conditions. As long as they do not deviate from the spirit of the present invention, all these substitutions or modifications should belong to the protection scope of the claims attached to the present invention.
Claims
1. A recycled aggregate treatment agent, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of polyvinyl alcohol, 5-15 parts of chitosan, 5-15 parts of polysiloxane, 6-10 parts of hydrophilic modified nano silica sol, 10-20 parts of penetrant and 60-80 parts of deionized water; the hydrophilic modified nano silica sol is prepared from the following components in parts by weight: 20-25 parts of nano silica, 0.3-0.4 parts of vinyl triethoxysiloxane, 0.5-1.0 parts of maleic anhydride, 2.0-4.0 parts of acrylic acid, 0.5-1 parts of hydroxyethyl acrylate, 0.1-0.3 parts of dibenzoyl peroxide, 0.1-0.3 parts of polyvinyl alcohol and 65-75 parts of anhydrous ethanol.
2. A recycled aggregate treatment agent according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 40 parts of polyvinyl alcohol, 10 parts of chitosan, 10 parts of polysiloxane, 8 parts of hydrophilic modified nano silica sol, 15 parts of penetrant and 67 parts of deionized water.
3. The method for preparing the recycled aggregate treating agent according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Preparation of hydrophilic modified nano-silica sol: Add nano-silica to anhydrous ethanol, stir at 40-50°C for 5-10 minutes, then add vinyl triethoxysiloxane, and continue to stir and react for 20-30 minutes; add maleic anhydride, acrylic acid, and hydroxyethyl acrylate again, continue to stir and react for 10-15 minutes, then add dibenzoyl peroxide, heat to 70-80°C and react for 2-3 hours; then add polyvinyl alcohol and stir until completely dissolved to obtain hydrophilic modified nano-silica sol; (2) dissolving polyvinyl alcohol in deionized water, stirring at 90-95° C. for 30-60 minutes, and cooling to obtain a polyvinyl alcohol solution; (3) Add chitosan, polysiloxane and hydrophilic modified nano-silica sol into the polyvinyl alcohol solution, stir and react at 50-60° C. for 20-40 minutes; then add the penetrant and stir evenly to obtain the product.
4. The method for preparing the recycled aggregate treating agent according to claim 3, characterized in that: In step (3), the penetrant is isobutyltriethoxysilane.
5. A recycled aggregate with excellent performance, characterized by: The product is obtained by treating recycled aggregate with the recycled aggregate treating agent according to any one of claims 1 to 2.
6. A method for processing recycled aggregate, characterized in that: The following steps are involved: (1) Stir the crushed waste concrete at 50-70°C for 20-40 minutes and rinse with water; Then stir at 50-70℃ for 20-40min, rinse with water, and the obtained recycled aggregate is ready for treatment; (2) soaking the recycled aggregate pretreated in step (1) in the recycled aggregate treatment agent according to any one of claims 1 to 2; (3) The recycled aggregate after soaking treatment is cleaned to remove impurities and dried.
7. The method for processing recycled aggregate according to claim 6, characterized in that: In step (2), the soaking treatment time is 12-24 hours.
8. The method for processing recycled aggregate according to claim 6, characterized in that: In step (3), the drying temperature is 50-60° C. and the drying time is 10-12 h.
Citation Information
Patent Citations
Treatment agent of recycled aggregate of waste concrete and treatment method
CN101624268A
Recycled aggregate modified by nano silicon dioxide as well as preparation method and application thereof
CN111892316A